Mogy - Povedák, István (Traditiones (Ljubljana), 2012)
During the last five years, the calendar of Hungarian festivals has turned upside down. Along with the wellknown rock festivals for the young (e.g., the Syiget festival), attended by hundreds of thousands every summer, a new type of cultural festival is gaining tremendous popularity in Hungary. The National Assembly of Hungarians (MOGY) is a patriotic/nationalist three-day event that attracts every segment of the Hungarian population, from teenagers to older generations.
Keywords: ethnology; Etnologija; national identity; Šege; Hungary; Narodna identiteta; Madžarska; ljudska kultura; kulturni festivali; ljudske šege; ljudski običaji; rituali